Software modeling application for verification of transportation planning engineering hypotheses. Issue 1 (April 2020) - Shchegolova, N; Talalai, V; Gorshenina, C; Smirnova, D
Abstract: The organization of traffic is a complex of engineering and organizational arrangements aimed at maximizing the use of traffic flows opportunities represented by the road geometric parameters and condition. The article deals with an example of using software modeling for creating a digital twin of a complex intersection in Saratov in order to verify the engineering hypotheses concerning the effective transportation planning. The current traffic situation in the PTV VISSIM program is simulated. The transportation planning engineering hypothesis proposed and simulated the solution options of changing the working traffic light duration at the intersection for verifying and widening the carriageway by adding a lane. The analysis of two models options allowed determining the most effective transportation planning measure in a given transport hub of the city with a high level of traffic delays, which is actually the duration change of the working traffic light at the intersection. The software modeling application is confirmed for creating a digital twin complex intersection in Saratov.